2021
DOI: 10.1038/s41467-021-26662-5
|View full text |Cite
|
Sign up to set email alerts
|

Focusing the electromagnetic field to 10−6λ for ultra-high enhancement of field-matter interaction

Abstract: Focusing electromagnetic field to enhance the interaction with matter has been promoting researches and applications of nano electronics and photonics. Usually, the evanescent-wave coupling is adopted in various nano structures and materials to confine the electromagnetic field into a subwavelength space. Here, based on the direct coupling with confined electron oscillations in a nanowire, we demonstrate a tight localization of microwave field down to 10−6λ. A hybrid nanowire-bowtie antenna is further designed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…The quantum sensor based on a nitrogen-vacancy (NV) center in diamond enables synchronous measurement of local magnetic field and temperature on VO 2 film, providing an unusual insight into the field-induced IMT (25,37). Meanwhile, conducting filaments composed of silver nanowires have been imaged by NV-center ensemble with high spatial resolution (24). Compared with the traditional methods (38)(39)(40)(41), this quantum sensing can provide a fundamentally different approach to imaging current-density distribution of conducting filaments in Mott materials, by detecting the induced stray magnetic fields (23)(24)(25).…”
Section: Properties Of Vo 2 Film and Imaging Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantum sensor based on a nitrogen-vacancy (NV) center in diamond enables synchronous measurement of local magnetic field and temperature on VO 2 film, providing an unusual insight into the field-induced IMT (25,37). Meanwhile, conducting filaments composed of silver nanowires have been imaged by NV-center ensemble with high spatial resolution (24). Compared with the traditional methods (38)(39)(40)(41), this quantum sensing can provide a fundamentally different approach to imaging current-density distribution of conducting filaments in Mott materials, by detecting the induced stray magnetic fields (23)(24)(25).…”
Section: Properties Of Vo 2 Film and Imaging Approachmentioning
confidence: 99%
“…The dynamic networks can operate by the competition between the channels in which the nucleation process of metal phase is crucial, similar to the algorithm of neural systems in which the neurons compete with each other to activate and connect to specific pathways encoded by synaptic plasticity (3,4). In addition, it is reported that quantum sensing can provide a fundamentally different approach to imaging the current-density distribution by detecting the induced stray magnetic fields with high spatial resolution and negligible disturbances, but the imaging of conducting filament in Mott material is still absent (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 2c, a nanowire-bowtie antenna on the diamond surface is adopted [23]. The two arms of the metallic bowtie structure are connected by a conductive wire with a width of approximately 1 µm.…”
Section: Detection Of Radio Signalmentioning
confidence: 99%
“…It hinders applications with a free space RF field. A potential solution is to utilize the quantum properties of interaction between nanoscale system and a weak electromagnetic field [21][22][23]. The coherent interaction between quantum emitter and the light field is recently applied for high resolution optical imaging with a low excitation power [24,25].…”
mentioning
confidence: 99%
“…Nitrogen-vacancy (NV) color centers are emerging solid-state quantum sensors that can measure several physical quantities using different detection protocols due to the influence of physical quantities variations such as magnetic field [1,2] , electric field [3] , temperature [4][5][6][7] , and stress [8] . With the advantages of high spatial and temporal resolution, high sensitivity, stable signal, and quantum performance at room temperature, NV color centers can provide an effective means of characterization in a variety of fields, including biomedicine [9] , dark matter [10] , electrochemical signals [11] , etc.…”
Section: Introductionmentioning
confidence: 99%